2020
DOI: 10.24925/turjaf.v8i11.2378-2387.3676
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Effects of Livestock Support Policies on Breeders: An Example of TR83 Region in Turkey

Abstract: This paper studied the effect of livestock support policies applied in Turkey by a emprical study. The study was carried out based on the analysis of the data collected through surveys with a total of 478 livestock enterprises in the TR83 region (including Amasya, Çorum, Samsun and Tokat provinces). The enterprises included in the survey study were grouped into three categories by the number of their animals. Binary Logistic Regression Model was applied in order to define the policy-based support payment utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Canbay (2021), who investigated production effect of agricultural supports between 1995 and 2018 in Turkey, found a statistically significant and positive relationship between agricultural supports and production in the short and long run. On the other hand, Erdal et al (2021) and Erdal et al (2020) showed that agricultural supports have effect not only on crop production but also on livestock existence.…”
Section: Agricultural Supports In Turkey and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Canbay (2021), who investigated production effect of agricultural supports between 1995 and 2018 in Turkey, found a statistically significant and positive relationship between agricultural supports and production in the short and long run. On the other hand, Erdal et al (2021) and Erdal et al (2020) showed that agricultural supports have effect not only on crop production but also on livestock existence.…”
Section: Agricultural Supports In Turkey and Literature Reviewmentioning
confidence: 99%
“…As a matter of fact, even if agricultural supports are decoupled, a great majority of the studies on the production effect of the agricultural supports confirm these findings. To give an example, O'Donoghue & Whitaker (2010), Weber & Key (2012), Becker & Judge (2014), Yildiz (2017), Canbay (2021), Erdal et al (2021) and Erdal et al (2020) suggested that the agricultural supports affect production positively. Especially, Katranidis & Kotakou (2008) and Haß (2021) concluded that production effects of coupled payments are more than decoupled payments.…”
Section: Conclusion and Policy Advicementioning
confidence: 99%
“…They have revealed that livestock support payments increase the supply of beef. Erdal et al (2020) debated the results of livestock supports by applying a survey on 478 livestock enterprises. According to the findings of the study, livestock supports are an important factor for 65% of livestock enterprises in order to increase their livestock presence.…”
Section: Literature Reviewmentioning
confidence: 99%